Case report: Intrapulmonary tidal volumes in a preterm infant with chest wall rigidity - Gaertner, Vincent D.; Restin, Tanja; Bassler, Dirk; Fauchère, Jean-Claude; Rüegger, Christoph M. (Frontiers in Pediatrics, 2022)
Background Chest wall rigidity is a known side effect of fentanyl use, which is why fentanyl is usually combined with a muscle relaxant such as mivacurium. Verifying endotracheal intubation is difficult in case of a rigid chest wall. Case presentation We present the case of a preterm infant (29 completed weeks gestation, birth weight 1150 grams) with a prolonged chest wall rigidity after fentanyl administration for intubation despite adequate doses of mivacurium. This resulted in a pronounced desaturation without any effect on heart rate. Clinically, the infant showed no chest wall movement despite intubation and common tools to verify intubation (including end-tidal carbon dioxide measurement and auscultation) were inconclusive. However, using electrical impedance tomography (EIT), we were able to demonstrate minimal tidal volumes at lung level and thereby, EIT was able to accurately show correct placement of the endotracheal tube. Conclusions This case may increase vigilance for fentanyl-induced chest wall rigidity in the neonatal population even when simultaneously administering mivacurium. Higher airway pressures exceeding 30 mmHg and the use of µ-receptor antagonists such as naloxone should be considered to reverse opioid-induced chest wall rigidity. Most importantly, our data may imply a relevant clinical benefit of using EIT during neonatal intubation as it may accurately show correct endotracheal tube placement.